Modeling and simulating the controller behavior of an automated people mover using IEC 61850 communication requirements - Kunz, Guilherme (2011)
Automated People Movers (APM) are systems for passenger transport with fully automated operation and high frequency service. Trains controllers are traditionally centralized and based on wired circuits, although they generally have serious difficulties in the installation and maintenance. As there is increased demand on the system, there are advantages in choosing an open architecture, with a simple communication system and distributed. These concepts are largely addressed in the development of IEC 61850. In this study we proposed the adaptation of the standard IEC 61850, design to be used in electric power systems to be applied in an APM system named Aeromovel installed in Porto Alegre, Brazil. Aeromovel is a nonconventional Automatic People Mover whose operation principle is based on pneumatics. A model, based on timed automata formalism, is proposed for IEC 61850 communications requirements and respective simulation results are presented.